LAYANAN KONSELING UNTUK MEREDUKSI STRESS AKIBAT PERCERAIAN ORANGTUA MENGGUNAKAN TEKNIK RESTRUKTURISASI KOGNITIF - Imas Nurlaela; Teti Sobari; Muhammad Rezza Septian (IKIP Siliwangi, 2022)
Stress is a response from oneself when faced with a problem. Stress can be caused by various things, one of which is from family factors. Parental divorce is one of these problems. Counseling services in reducing stress due to parental divorce use cognitive restructuring techniques. The purpose of this study was to determine the implementation of counseling services to change negative thoughts into positive ones.The research was conducted at the South Bandung Vocational School, Bandung City. The method used is descriptive qualitative. The subjects in this study were students whose parents had divorced. The counseling service technique used is cognitive restructuring. Counseling are conducted 6 times for 2 weeks.The results of the research that have been carried out show that the counselor is appropriate to follow the service steps using cognitive restructuring cognitive techniques. Students feel a change starting with negative thinking can turn into a positive one. Counseling services can help counselees to change their negative thoughts into positive ones.Keyword: Stress, Parental Divorce, Cognitive Restructuring Techniques.